Inappropriate Doses of Intravenous Polymyxin B after Renal Adjustment Lead to Treatment Failure - Bahiah Ismail; Mohd Nazri Shafei; Azian Harun; Saedah Ali; Mahamarowi Omar; Zakuan Zainy Deris (Universidade de São Paulo, 2021)
Sub-therapeutic doses, shorter duration of therapy, female gender, bacteremia, and renal impairment were among independent predictors of polymyxin B treatment failure. In this study, we found an association between inappropriate doses of polymyxin B (<15000 or >25000 unit/kg/day) and renal impairment. Inappropriate doses of polymyxin B were significantly associated with CrCl 20-50 mL/min (p = 0.021, ORadj 6.660, 95% CI 1.326, 33.453) and CrCl <20 mL/min (p = 0.001, ORadj 22.200, 95% CI 3.481, 141.592). By conducting sub-group analysis only using subjects with appropriate dosage, renal impairment was not associated with polymyxin B treatment failure, thus indicating that treatment failure was due to an inappropriate dose of polymyxin B, rather than renal impairment. In conclusion, renal impairment was not directly associated with treatment failure but was due to an inappropriate dosage of polymyxin B after renal adjustment